The Effect Of Oxytocin Massage On Milk Production For Breastfeeding Mothers In The Working Area Of The Puskesmas Syamtalira Bayu North Aceh District - Myrna Lestari; Cut Linar (Jurnal EduHealth, 2024)
Breast milk production is greatly influenced by psychology, mothers who are always in a state of stress, sadness, lack of self-confidence and various forms of emotional tension will reduce the volume of breast milk and even breast milk production will stop altogether.. The aim of this research is todetermine the effect of oxytocin massage on breast milk production in breastfeeding mothersSyamtalira Bayu Community Health Center Working Area, North Aceh Regency.The design of this research is analytical research using a cross sectional approach.The population in this study were all breastfeeding mothers who were inSyamtalira Bayu Health Center Working Areatotaling 40 breastfeeding mothers.The sampling method in this research is to use the total population. Where the sample for this research is the entire population, totaling 40 respondents. The validity test in this research will be carried out in the Mongeudong Community Health Center Area with a total of 10 respondents, 30 questions with an r product moment value of 0.70. The research results showed that of the 28 breastfeeding mothers who did oxytocin massage, the majority of their breast milk production was smooth, namely 17 people (60.7%), while of the 12 breastfeeding mothers who did not do oxytocin massage, the majority of their breast milk production was not smooth, namely 9 people (75%). It is hoped that this will increase respondents' knowledge in efforts to increase breast milk production and provide information on the impact of failure in the breastfeeding process.